Contribution of dissolved organic matter to seawater salinity measured by optic refractometer: a case study of DOM extracted from Aoshan Bay - Zhang, Cong; Xiao, Yuyang; Gao, Wenyue; Fu, Yujie; Zhou, Zhensong; Chen, Shiyu; Su, Juan; Wu, Chi; Wu, Albert (Frontiers in Marine Science, 2023)
Dissolved organic matter (DOM) in seawater, consisted of a complex mixture of compounds and accounted for about 90% of marine organic carbon, is an important part of the global carbon cycle and also a part of absolute salinity of seawater. As the components of DOM are non-ionized in seawater, electric conductivity measurement cannot observe its contribution to salinity, which could lead to measurement error in salinity. Salinity measurement based on optic refractive index could reveal contribution of all dissolved matters in seawater including both non-ionized and ionized components. In this paper, a comparative study of DOM contribution to the salinity measurement by optic refractive index method and electric conductivity method was carried out for the first time. Adding DOM, extracted from Aoshan Bay, Qingdao, China, into Chinese Standard Seawater, our experimental results showed an increase of optic refractive index at 1.19×10-4 ± 4×10-6 per 1g/kg of DOM, which corresponds to a practical salinity increase of 0.697 ± 0.036 PSU per 1 g/kg of DOM. While, the conductivity of seawater measured by a conductivity-temperature sensor showed a decrease of 0.00065 ± 0.00008 mS/cm per 1 g/kg of DOM, which corresponded to a decrease of salinity at 0.00052 ± 0.00007 PSU per 1 g/kg of DOM. By comparing the optic and electric measurement results, the contribution of non-conductive components in the dissolved organic matters to salinity could be distinguished, which has great significance for the measurement of absolute salinity, global carbon cycle etc.